Pengaruh Aging Paduan Al-Si-Cu Bahan Wajan Produk IKM Terhadap Struktur Mikro dan Sifat Mekanik - Kartikasari, Ratna; Teddy Marvin Silalahi; Wartono (ReTII, 2022)
This research is one of the efforts to improve the quality of IKM products pan by providing heat treatment to aluminum alloy as a frying pan material. The treatment process given is aging (age hardening) with the aim that the alloy has an increase in tensile strength, hardness, ductility and changes the microstructure into finer grains. The material used in this research is aluminum alloy Al-Si-Cu with different levels of Cu ranging from 2%, 4% and 6%. The aging is carried out in the first stage, namely heating at a temperature of 525 ÂºC for 1 hour, followed by cooling in water media. Then the Al-Si-Cu alloy was reheated at a temperature of 195ÂºC for 5 hours and then cooled in air. The tests carried out were microstructure test using an optical microscope, Brinell test, tensile test and impact test using the Charpy. The microstructure shows that the Al-Si-Cu alloy has Al, Si and CuAl2. The highest hardness value was found aging addition of 4% Cu at 21.63 BHN. The tensile test results show that the highest stress value occurs in the 4% Cu alloy with aging of 18.93 MPa and strain value of 0.94%. Impact testing resulted in the highest impact value on raw material with 2% Cu content of 0.007 J/mm2.